Put pressure worldwide on blood pressure control - Costanzo, Simona; de Gaetano, Giovanni; Iacoviello, Licia (Journal of Thoracic Disease, 2016)
There is a close relationship between high blood pressure (BP) levels and the risk of cardiovascular disease (CVD) and chronic kidney disease (1). The risk of these clinical outcomes is lowest at a BP of around 115/75 mmHg.